2017
DOI: 10.1186/s12872-017-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between periodontal disease and the risk of myocardial infarction: a pooled analysis of observational studies

Abstract: BackgroundSeveral meta-analyses have indicated that periodontal disease (PD) are related to cardiovascular diseases (CVDs). However, the association between PD and myocardial infarction (MI) remains controversial. Here we aimed to assess the association between PD and MI by meta-analysis of observational studies.MethodsPubMed, EMBASE and the Cochrane Library were searched through July, 2016. Observational studies including cohort, cross-sectional and case–control studies reporting odds ratio (OR) or relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 48 publications
2
49
0
5
Order By: Relevance
“…Other proinflammatory states are more common in lower socioeconomic position groups and could play a role in the pathogenesis of kidney disease. For example, periodontal disease is socially patterned and has been consistently linked with cardiovascular disease (38,39), diabetes (40), and systemic autoimmune diseases (41,42). An association with all-cause CKD has also been described, although the relationship between periodontal disease and specific kidney diseases has not been well studied (43).…”
Section: Discussionmentioning
confidence: 99%
“…Other proinflammatory states are more common in lower socioeconomic position groups and could play a role in the pathogenesis of kidney disease. For example, periodontal disease is socially patterned and has been consistently linked with cardiovascular disease (38,39), diabetes (40), and systemic autoimmune diseases (41,42). An association with all-cause CKD has also been described, although the relationship between periodontal disease and specific kidney diseases has not been well studied (43).…”
Section: Discussionmentioning
confidence: 99%
“…39 A meta-analysis of observational studies including 22 observational studies including 129,630 participants showed that patients with periodontitis have an increased risk of MI (OR 2.02, 95% CI 1.59-2.57). 40 A systematic review to investigate the effects of periodontal therapy in preventing the occurrence of, and management or recurrence of, CVD in patients with chronic periodontitis 41 found very low quality evidence that was insufficient to support or refute whether periodontal therapy can prevent the recurrence of CVD in the long term in patients with chronic periodontitis. No evidence on primary prevention was found.…”
Section: Clinical Conditions Affecting Cardiovascular Riskmentioning
confidence: 99%
“…There is strong evidence that untreated oral diseases and disorders not only negatively affect general health but also increase the probability of diabetes and cardiovascular diseases [4,5]. A meta-analysis of follow-up studies estimated that poor oral health and periodontal diseases may increase the risk of such diseases by approximately 20% [6].…”
Section: Introductionmentioning
confidence: 99%